Morris goes to school - Wiseman, Bernard (New York : Harper & Row, 1983)
Morris the moose has an exciting day in school learning the alphabet, counting, singing, spelling, and doing other things that make him a unique moose.
A Harper Trophy book.
Keywords: Civil society; Social contract; Moose -- Fiction